Simulation: Art or science? How to teach it?. (26th May 2009) - Molnar, Istvan; Moscardini, Alfredo O.; Breyer, Reiner
This paper discusses the underlying philosophy of simulation education. It discusses the skills needed by the user to simulate and provides a survey of some important simulation methodologies and software tools. Simulation can be seen as a three-step process of building a model of a system, computing/evaluating the model on a digital computer, and transferring the model solution back to the system under investigation. Analysing the three-step process of simulation, we conclude that in different phases of modelling and simulation, different scientific or artistic characteristics are predominant. The paper puts forward the view that simulation is more of an art than a science and that this viewpoint has major consequences for its pedagogy.